Pedagogues and Social Workers - Challenges of Collaboration - Ljubetić, Maja; Vukušić, Anita Mandarić; Pezo, Katarina (European Scientific Journal, ESJ, 2018)
In their work, pedagogues and social workers respond to many pedagogical and social challenges that children and/or their families face. In order to successfully address these challenges, it is necessary to achieve a quality collaboration between the school and the social welfare centre. Seeking an answer to the question of quality of the collaboration, three research questions were asked in this research. The answer was reached using a semi-structured interview. The results showed that research participants assessed the following as important: collaboration (they also offered suggestions on how it could be improved), their own education and training, personality traits and personal views of “helpers”, the need to harmonise legislation and to employ social workers in schools as members of professional counselling services.